Role of Culture in Communication Process and Atmosphere of Business Negotiation: A comparative Analysis of Business Negotiations in CEE and ASEAN Countries from Finnish Firms' Perspective - Kolomy, Andrew (My University, 2014)
In the research area of cross-cultural business negotiations there are few studies on factors that impact the atmosphere and the communication process of business negotiations. Hence, the interest of this study lies in investigating specifically what are the cultural and strategic factors and to what extent they determine the nature of the atmosphere and communication in particular business negotiations. The targeted negotiations are of Czechs and Malaysians, considered from the Finnish firms’ perspective. Furthermore, none of such academic research has ever been made. Thus, this study aims to answer the research question, which is to identify and compare similarities and differences in the communication process and the atmosphere in Czech and Malaysian business negotiations. The theoretical framework of this study consists of specific cultural and strategic factors that determine the final nature of the atmosphere and the communication process. This study applies a qualitative research method with a multiple-case study research strategy. Two Finnish firms were chosen as case companies, and the empirical data was collected by conducting semi-structured interviews with Finnish high-level managers who were involved in Czech or Malaysian business negotiations. The findings of this study demonstrate there are in fact more similarities between Czech and Malaysian negotiators than proposed in the theory. The nature of the atmosphere and the communication are affected by particular cultural and strategic factors relevant for each of the countries. On the side of Czech negotiators, a corporate culture and mix of two cultures play a role of major determinants. Malaysian negotiations were observed more heterogeneous, mainly due to existence of various ethnic and religious groups, a change in a Malaysian society towards Western values, and other factors that appeared to be culturally or strategically related.
Keywords: Culture and business negotiation; Atmosphere; Communication; Czech Republic; Malaysia; fi=Master's Degree Programme in International Business|